Pseudo-Thrombotic Microangiopathy Secondary to Vitamin B12 Deficiency - Dylan Morrissey; Yuheng Sun; Sarina Koilpillai; Jacqueline Kropf; Steve J. Carlan (Case Reports in Medicine)
Background. Clinical B12 deficiency with hematological or neurological manifestations is rare. An unusual manifestation of B12 deficiency is pseudo-thrombotic microangiopathy (TMA), which is characterized by hemolytic anemia, thrombocytopenia, and schistocytosis and only occurs in 2.5% of those with B12 deficiency. Pseudo-TMA is misdiagnosed as thrombotic thrombocytopenic purpura (TTP) in 40% of cases, resulting in misguided treatment including plasmapheresis. Case. A 44-year-old Hispanic presented with 3 weeks of progressively worsening non-radiating chest pain, fatigue, and shortness of breath (SOB). Laboratory findings revealed severe pancytopenia and macrocytosis with a hemoglobin of 5.4 g/dL, mean corpuscular volume of 116.3 fL, and vitamin B12 low at 149 pg/mL. She was diagnosed with pseudo-TMA and after starting 1000 micrograms of parenteral vitamin B12 injections daily and discontinuing plasmapheresis and steroid administration, she improved. Conclusion. Failure to recognize pseudo-TMA often results in unnecessary treatment with plasmapheresis and delays appropriate treatment with vitamin B12 supplementation. It is therefore extremely important to consider pseudo-TMA as a differential diagnosis in patients that present with hemolytic anemia, thrombocytopenia, and schistocytosis.